THE INFLUENCE OF PEDAGOGICAL COMPETENCE ON TEACHER PERFORMANCE AT UPT SMK NEGERI 5 SIDENRENG RAPPANG - Purnamasari, Dewi; Makmur, Mariam; Suriadi, Suriadi (Universitas Ichsan Sidenreng Rappang, 2024)
Teacher pedagogical competence is not only essential as an effort to improve the quality of teaching, but also as a strategic effort in managing competent and responsive human resources. The purpose of the study was to determine whether Pedagogic Competence affects Teacher Performance at UPT SMK Negeri 5 Sidenreng Rappang. The research method used is quantitative. The data used primary data obtained from questionnaires. The population of this study was 60 respondents, sampling using saturated sampling, the data obtained was processed using the SPSS programme. The data analysis method used is simple regression analysis. The results of the study interpret that Pedagogic Competence at UPT SMK Negeri 5 Sidenereng Rappang has a significant effect on Teacher Performance, so that the hypothesis in this study is accepted.